Placental Extracellular Vesicles and Feto-Maternal Communication - Tong, M. (Cold Spring Harb Perspect Med, 2015)
The human placenta is an anatomically unique structure that extrudes a variety of extracellular vesicles into the maternal blood (including syncytial nuclear aggregates, microvesicles, and nanovesicles). Large quantities of extracellular vesicles are produced by the placenta in both healthy and diseased pregnancies. Since their first description more than 120 years ago, placental extracellular vesicles are only now being recognized as important carriers for proteins, lipids, and nucleic acids, which may play a crucial role in feto-maternal communication. Here, we summarize the current literature on the cargos of placental extracellular vesicles and the known effects of such vesicles on maternal cells/systems, especially those of the maternal immune and vascular systems.